Ripples in Water - Heller, Esther (Denmark, 2000)
A story about women working together on grass roots level across borders in order to establish a shelter in Vilnius, Lithuania, for female victims of domestic violence.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films